2003
DOI: 10.1103/physrevlett.90.106104
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Optical Sensitivity to Adsorption due to Depolarization of Anisotropic Surface States

Abstract: Reflectance difference spectroscopy is used to probe the optical transitions between surface states on the Cu(110) surface. Upon deposition of smallest amounts of carbon monoxide (CO) the signal is strongly quenched, which translates into a huge cross section of the order of 1000 A(2) for a single adsorbed CO molecule. This strongly enhanced surface sensitivity is interpreted as the loss in anisotropy (depolarization) of the surface states due to scattering from the adsorbed CO molecules. This feature renders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…15) on Cu (110), that the typically observed non-linear reduction in the intensity of the 2.1 eV RAS peak with increased molecular coverage is primarily the result of the depolarization of the associated p-like occupied surface state caused by electrons within this state scattering isotropically from adsorbed molecules-the process responsible for the standing-wave patterns observed around various nanostructures in the STM images produced by Crommie et al 2,3 However, the low-temperature IPES work of Heskett et al 16 on Cu (110) indicates that individual surface defects destroy the unoccupiedȲ surface state at a rate proportional to a considerable surrounding area. Thus the rapid destruction of surface-state-related RAS features with surface defect coverage could be explained by either the electron-scattering effect proposed by Sun et al,9 or the destruction of the unoccupied surface state involved. At this stage it is not clear which effect, if either, has the dominant influence.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…15) on Cu (110), that the typically observed non-linear reduction in the intensity of the 2.1 eV RAS peak with increased molecular coverage is primarily the result of the depolarization of the associated p-like occupied surface state caused by electrons within this state scattering isotropically from adsorbed molecules-the process responsible for the standing-wave patterns observed around various nanostructures in the STM images produced by Crommie et al 2,3 However, the low-temperature IPES work of Heskett et al 16 on Cu (110) indicates that individual surface defects destroy the unoccupiedȲ surface state at a rate proportional to a considerable surrounding area. Thus the rapid destruction of surface-state-related RAS features with surface defect coverage could be explained by either the electron-scattering effect proposed by Sun et al,9 or the destruction of the unoccupied surface state involved. At this stage it is not clear which effect, if either, has the dominant influence.…”
Section: Introductionmentioning
confidence: 97%
“…Surface-state-related RAS features such as this are well known to be highly sensitive to molecular adsorption, [8][9][10] temperature, 10-12 surface alloying, 13 and the creation of surface defects via heating 14 and ion bombardment at low temperatures. 10 It has been suggested by Sun et al, in studies focusing on the adsorption of CO (Ref.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the RDS signal at 2.1 eV is extremely sensitive to surface defects due to the large lateral extent of the quasi-free electron nature of the metal surface states involved in the corresponding optical transition. Indeed, a cross section as large as 1000 A 2 for a single isolated CO molecule adsorbed on Cu(110) has been determined by RDS [5]. This means that the initial quenching of the RDS signal at 2.1 eV is about 100 times larger than expected from the geometric size of a single molecule.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, RDS has also been applied to metal surfaces such as Cu(110) [1,2,3,4,5], Ag(110) [6] and Au(110) [7]. In particular, the RDS spectrum of Cu(110) shows several distinct features, which are related to a surface state transition at 2.1 eV, a surface resonance transition at 4.12 eV and two surface modified bulk state transitions at 2.2 eV and 4.4 eV [2].…”
Section: Introductionmentioning
confidence: 99%
“…In recent work focusing on Ag (110) [3], we have simulated the effect of thermally created surface defects on the intensity of the surface state-derived 1.7 eV RAS peak and have shown that individual adatoms have the ability to quench the contribution to the intensity of this feature over a significant surrounding area. Similarly, Sun et al [4,5] have revealed that molecular adsorbates induce an equivalent effect on the 2.1 eV Cu (110) RAS peak. These studies demonstrate that surface state related RAS features have the potential to be used for accurately monitoring a variety of surface kinetic processes such as the creation of thermal ad atoms from step edges and the ordering of molecular adsorbates.…”
mentioning
confidence: 94%